Can revenue collection for public funding in health care be progressive? An assessment of 29 Countries - Rice, Thomas; Vrangbæk, Karsten; Saunes, Ingrid S; Bouckaert, Nicolas; Bryndová, Lucie; Cascini, Fidelia; Võrk, Andres; Dimova, Antoniya; Kocot, Ewa; Murauskiene, Liubove; Bricard, Damien; Blumel, Miriam; et al. (Health policy (Amsterdam, Netherlands), 2024)
Most research on health care equity focuses on accessing services, with less attention given to how revenue is collected to pay for a country's health care bill. This article examines the progressivity of revenue collection among publicly funded sources: income taxes, social insurance (often in the form of payroll) taxes, and consumption taxes (e.g., value-added taxes). We develop methodology to derive a qualitative index that rates each of 29 high-income countries as to its progressivity or regressivity for each of the three sources of revenue. A variety of data sources are employed, some from secondary data sources and other from country representatives of the Health Systems and Policy Monitor of the European Observatory on Health Systems and Policies. We found that countries with more progressive income tax systems used more income-based tax brackets and had larger differences in marginal tax rates between the brackets. The more progressive social insurance revenue collection systems did not have an upper income cap and exempted poorer persons or reduced their contributions. The only pattern regarding consumption taxes was that countries that exhibited the fewest overall income inequalities tended to have least regressive consumption tax policies. The article also provides several examples from the sample of countries on ways to make public revenue financing of health care more progressive.
Keywords: Financing, Government; sociální zabezpečení; Social Security; Income Tax; Delivery of Health Care; poskytování zdravotní péče; daň z příjmu; daně; Humans; vyspělé země; Taxes; Developed Countries; lidé; financování vládou